The Potential of Catechin-Containing Plants as Antihyperlipidemic Treatment: A Review - Riyadh Aqilsya Amaryl Dyas; Fitra Romadhonsyah; Pinus Jumaryatno (Universitas Hamzanwadi, 2025)
Hyperlipidemia is a condition characterized by elevated levels of cholesterol and triglycerides. Hyperlipidemia can lead to vascular disorders affecting the heart and brain, potentially resulting in severe complications such as coronary heart disease and stroke. A range of treatment strategies are employed to manage this condition encompassing the use of drugs as well as traditional medicinal approaches. Among these, the use of medicinal plants presents a promising option which considering relatively safe owing to their natural origin and minimal risk of significant side effects, as well as their bioactive compounds. Catechin is one of secondary metabolites commonly found in plants which showed various biological activities that potential for medicinal use. The aim of this review was to provide a comprehensive review of existing literature regarding the catechin-containing plants in lowering cholesterol and triglyceride levels. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was employed to select literature obtained from reputable online databases such as Google Scholar, PubMed and Science Direct which were published from 2015 to 2025. A narrative analysis was performed to assess the selected literatures. Based on literature screening, 200 articles were identified of which 14 were selected for inclusion in the review based on predefined criteria. This study highlighted the therapeutic potential of medicinal plants containing catechins which exhibit efficacy in reducing cholesterol and triglyceride levels. Medicinal plants may offer an effective herbal remedy for reducing cholesterol and triglyceride levels, with catechins may have a contribution to this activity.